Maine’s Innovation Prospects: What the Research Can Tell Us - Silka, Linda (Maine Policy Review, 2014)
The innovation literature suggests Maine faces a number of challenges. This overview article discusses this literature, noting how recent findings about boundary spanning point to the importance of both individual skills and group collaboration in innovation. It highlights the implications for policies that could jumpstart innovation, noting the importance of looking to history, looking across topics, looking across disciplines, looking to other states, and looking to other countries to avoid becoming too short-sighted and parochial in approaches.